2020
DOI: 10.17509/edukid.v16i2.19830
|View full text |Cite
|
Sign up to set email alerts
|

Penyelenggaraan Pendidikan Inklusif Di Lembaga Paud

Abstract: Penelitian ini dilatarbelakangi oleh jumlah ABK yang semakin meningkat dan penyelenggaraan pendidikan inklusi di lembaga PAUD yang masih sedikit serta penelitian terdahulu yang masih sangat terbatas. Tujuan penelitian ini untuk mengetahui penanganan ABK di PAUD berbasis alam. Penelitian ini menggunakan pendekatan kualitatif dengan desain penelitian studi kasus. Teknik pengumpulan data dilakukan melalui wawancara pada tiga partisipan yaitu: kepala sekolah, fasilitator kelas, dan GPK. Analisis data menunjukkan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
3
0
3
Order By: Relevance
“…In Indonesia, the classifications commonly used are: ( 1 Inclusive education has been rolling out for more than a decade in Indonesia, however, there are still some problems in its implementation, both in terms of the availability of human resources and infrastructure, as research conducted by Wirantho and Arriani (2017:15) regarding inclusive education services in PAUD found that: inclusive education in PAUD has been running even though there are no regulations that specifically regulate inclusive education in PAUD in the sense that it is not yet operational compared to primary and secondary education; b) overlapping regulations between ministries; the services provided for ABK in PAUD are not integrated across ministries and involve units below them (Regional Government Work Units -SKPD), c) some PAUD refuse to accept ABK in PAUD units due to limited human resources and infrastructure. This is in line with the research of Azizah et. al (2019) which states that one of the problems in implementing inclusive education in PAUD is the unavailability of facilities and human resources.…”
Section: Introductionsupporting
confidence: 93%
“…In Indonesia, the classifications commonly used are: ( 1 Inclusive education has been rolling out for more than a decade in Indonesia, however, there are still some problems in its implementation, both in terms of the availability of human resources and infrastructure, as research conducted by Wirantho and Arriani (2017:15) regarding inclusive education services in PAUD found that: inclusive education in PAUD has been running even though there are no regulations that specifically regulate inclusive education in PAUD in the sense that it is not yet operational compared to primary and secondary education; b) overlapping regulations between ministries; the services provided for ABK in PAUD are not integrated across ministries and involve units below them (Regional Government Work Units -SKPD), c) some PAUD refuse to accept ABK in PAUD units due to limited human resources and infrastructure. This is in line with the research of Azizah et. al (2019) which states that one of the problems in implementing inclusive education in PAUD is the unavailability of facilities and human resources.…”
Section: Introductionsupporting
confidence: 93%
“…To overcome these problems, inclusive schools usually minimize them by providing individual learning programs (Azizah et al, 2020;Heldanita, 2018). This is in line with research conducted which states that the individual learning programs is recognized as a strategy tailored to the needs of children with special needs.…”
Section: Challenges In Integrating Music Learning Methods In Inclusiv...mentioning
confidence: 67%
“…Over time, many countries adopt regulations and policies of inclusive education. For example, Individuals with Disability Education Act/IDEA is a vital step to promote inclusive education (Azizah et al, 2020;Heldanita, 2018). Excellent comprehension on child diversity and various special needs that might be possessed by children has brought inclusive education to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…In order to fulfill educational objectives and inclusion principles in accordance with the Regulations of Minister of National Education No. 70 of 2009 Article (1) concerning inclusive education [18], that inclusive education is an implementation system education for all students who have disabilities and have the potential for intelligence and/special talents to participate in education or learning in one educational environment together with students in general [19]. So, the school system needs to ensure the availability of resources is needed to support children's learning needs, while teachers need to be aware of their students' educational needs.…”
Section: Resultsmentioning
confidence: 99%